(untitled) (International Journal of Engineering and Computer Science, 2017)
The history of sensor network technology originates in the first distributed sensing idea implementations. The continuous work of researchers and engineers over sensor networks which lately became wireless sensor networks (WSNs). Wireless sensor network is one of the g r owi n g technology for sensing and performing the different tasks. Such networks are beneficial in many fields, such as emergencies, health monitoring, environmental control, military, industries and these networks prone to malicious users’ and physical attacks due to radio range of network, un-trusted transmission, unattended nature and get access easily. Security is a fundamental requirement for these networks. In this paper, our center of attention is on physical attacks and issues in wireless sensor networks. Through this review, easily identify the purpose and capabilities of the attackers. Further, we discuss well-known approaches of security detection against physical attacks. The template is used to format your paper and style the text. All margins, column widths, line spaces, and text fonts are prescribed; please do not alter them.